The Concept of Entrepreneurship in a Business Perspective - Priyadi, Hilman; Mulyani, Ana Susi (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
This material discusses the concept of entrepreneurship, theories that support the understanding of entrepreneurial phenomena, as well as the characteristics inherent in entrepreneurship. Entrepreneurship is defined as the process of creating something new, innovative and valuable. There are four main theories: economic, sociological, psychological, and behavioral, which provide different views on entrepreneurship. The concept of entrepreneurship includes the risk manager's ability to optimize resources to create useful products or businesses. Several definitions of entrepreneurship are presented by experts such as Ahmad Sanusi, Peter F. Drucker, and Soeharto Prawiro. Entrepreneurial characteristics include high commitment, creativity, innovation, independence, and perseverance. Through understanding these concepts and characteristics, society can respond to changing needs and realities with high initiative and creativity.